Accompany the sick in the prelude to the end of its life cycle - Maria Teresa Miret García; Álvaro Bernalte Benazet (Universidad de Alicante, 2014)
Objective: Perform an ethnography, palliative unit, to study the interactions of the actors, in particular that of doctors with patients, who are living this particular situation of transit to death; and the opinion of those on palliative care. Methodology: The paradigm that we ascribe is the qualitative, ontologically constructivist and epistemologically, from the point of view of the sociologies of life, still our method of Ethnography. Results: From the speech, mostly from interviews with doctors have been collected verbatim. Conclusions: Among other things, on the stage, a microspace within the Hospitalito, called care media unit, represents going back at other times the dichotomy thesis / antithesis, the thesis that it was a unit that it had formally inaugurated as a palliative unit, we assume that with a propaganda purpose, but the antithesis was the reality, and this was without a doubt that he was still a unit of care means.